ChemInform Abstract: Synthesis and Antitumor Activity of Novel 4‐(2‐Fluorophenoxy)quinoline Derivatives Bearing the 4‐Oxo‐1, 4‐dihydroquinoline‐3‐carboxamide Moiety. Issue 45 (14th October 2013) - Li, Sai; Jiang, Rui; Qin, Mingze; Liu, Haicheng; Zhang, Guangyan; Gong, Ping
Abstract 19 Title compounds with the skeleton of (X) carrying a variety of substituents and cyclic amine components are prepared and tested for their antitumor activities.